The Foreign Exchange Auction System’s Effect on SME Stability and Performance - Chikwira, Collin (International Journal of Economics and Financial Issues, 2023)
This study investigates the impact of foreign exchange auction systems on the viability and efficiency of small and medium-sized businesses (SMEs) in developing countries. This investigation uses a quantitative approach using a vector error correction model (VECM) for time series data. The results of SMEs growth and forex auction usage fail to show either a long-run or a short-run link, but they do reveal unidirectional causation running from forex auction usage to SMEs growth. The log of real SMEs’ measure of economic activities and the log of SMEs loans as a measure of loans to SMEs have a unidirectional causation impact in the short run. This indicates that lending activities and the growth of SMEs have a causal effect on bank lending in the short run. The findings shed light on how the foreign exchange auction system can effectively be constructed to benefit small and medium-sized enterprises (SMEs), stimulate their growth, and support the stability of their economies in developing nations.